Selected Heavy Metal Levels in Cereals in Fluorspar Mining Belt, Elgeyo Marakwet County in Kenya - Olero, J. N. Kemboi; Simiyu, G. M.; Kipkorir, E. C.; Wakhisi, J. (Africa Environmental Review Journal, 2022)
Minerals in the earth crust get exposed to the environment through mining. Food crops grown on the contaminated soils bio-accumulate the metals posing adverse effects to the consumers. The study was aimed at investigating the concentrations of Arsenic (As), Cadmium (Cd), Chromium (Cr) and Lead (Pb) in cereals (maize, millet and beans) collected from three zones in Fluorspar mining belt in Kimwarer sub-catchment. A total of 60 food samples were collected from the households and analyzed using Flame Atomic Absorption Spectrophotometer (AAS) for Cd, Cr and Pb while As was analyzed using Atomic Absorption Spectrophotometer coupled with Vapour Generating component. Data was analyzed using ANOVA and Students New Kaules (SNK). The levels of Arsenic, Cadmium and Lead varied significantly (P<0.05, α=0.05) in millet between Upper and Lower Kimwarer and also between Middle and Lower Kimwarer.The metal mean concentrations of Arsenic, Cadmium and Lead in food were above levels recommended by CODEX Alimentarius International Food Standards in all the zones. Ingestion of the selected heavy metals above the recommended levels poses health risks to the consumers living within the Fluorspar mining area. It’s therefore recommended that the Ministry of Public Health should advise farmers to avoid planting and consuming food grown within the contaminated soils in Kimwarer mining belt.